2019
DOI: 10.1111/nyas.14263
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin‐independent constitutive endocytosis of GPR125/ADGRA3

Abstract: The orphan receptor GPR125 (ADGRA3) belongs to subgroup III of the adhesion G protein−coupled receptor (aGPCR) family. aGPCRs, also known as class B2 GPCRs, share basic structural and functional properties with other GPCRs. Many of them couple to G proteins and activate G protein−dependent and −independent signaling pathways, but little is known about aGPCR internalization and β-arrestin recruitment. GPR125 was originally described as a spermatogonial stem cell marker and studied for its role in Wnt signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
2
20
1
Order By: Relevance
“…Thus, it was proposed that these genes may serve as potentially novel biomarkers of AML, pending further validation in additional patients, and in vitro and in vivo experimental models of AML. ADGRA3, also known as GPR125 is an adhesion G-protein-coupled membrane receptor, which mediates downstream signaling pathways by activation of G proteins (22). With respect to the role of ADGRA3 in AML, it has been reported that its protein product, GPR125, is downregulated in AML, in contrast to the results of the present study, suggesting that the exact role of this gene in AML requires further study (23).…”
Section: Discussioncontrasting
confidence: 86%
“…Thus, it was proposed that these genes may serve as potentially novel biomarkers of AML, pending further validation in additional patients, and in vitro and in vivo experimental models of AML. ADGRA3, also known as GPR125 is an adhesion G-protein-coupled membrane receptor, which mediates downstream signaling pathways by activation of G proteins (22). With respect to the role of ADGRA3 in AML, it has been reported that its protein product, GPR125, is downregulated in AML, in contrast to the results of the present study, suggesting that the exact role of this gene in AML requires further study (23).…”
Section: Discussioncontrasting
confidence: 86%
“…Other GPCRs also internalize constitutively without the need for arrestins, but their exact mechanisms are not defined. Using enzyme-linked immunosorbent assay (ELISA) and confocal microscopy, the orphan adhesion receptor ADGRA3 (previously called GPR125) was found to undergo rapid constitutive internalization in an arrestinindependent, but clathrin-dependent manner (Spiess et al, 2019). The internalized receptor colocalized with transferrin receptor 1 in early endosomes.…”
Section: Arrestin-independent Constitutive Endocytosismentioning
confidence: 99%
“…Though less well understood, recent discoveries of involvement of aGPCRs in human disease has produced a growing interest in their therapeutic potential (33). Although Gpr125 is an orphan receptor evidence has emerged recently suggesting a role in receptor trafficking and endosomal signaling (28).…”
Section: Gpr125 Is Essential For the Generation Of A Functional Tear mentioning
confidence: 99%
“…Previous studies have highlighted Gpr125 as a marker of undifferentiated murine spermatogonial progenitors (23), documented its elevation in the choroid plexus following injury and correlated its high expression with both good and poor outcome in cancer (24)(25)(26). Ectopic expression of Gpr125 has shown that in zebrafish it modulates Wnt/planar cell polarity processes by interacting with the cytoplasmic adaptor Disheveled (Dsh), and in cultured cells undergoes constitutive clathrin-mediated internalization to endosomes (27,28). However, the physiological function of native Gpr125 has remained elusive.…”
Section: Introductionmentioning
confidence: 99%